(3CSeGA GdeOdSjf ef QLGd GdMOjKs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3YHOGddg GdLGhi s)
(3ChdgG (B:s
(3hHYO agPg QSGdI dWjaI JTJed Ydi CSeGA GdeOdSjf ef QLGd GdMOjK Ydi CMQa GdeYLe s
(3BNQgG (B:s
(3hQhi Yf YHOGddg Hf eZad Yf GHf eSYhO GfJgi s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B148 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B185 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B30 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs